Physical and biomechanical relationships with countermovement jump performance in team sports: Implications for athletic development and injury risk - Bygate-Smith, M. K.; Beaven, C. M.; Drury, M. (Sports, 2025)
Background: Several physical qualities have been linked to countermovement jump (CMJ) performance. However, the relative importance of each of these factors is unclear. (1) Objectives: The present systematic review sought to evaluate the characteristics associated with CMJ performance in adult team-sport athletes. (2) Methods: A comprehensive search of three databases and the grey literature yielded 18 articles that met the inclusion criteria. Pearson`s correlation coefficient was used to assess statistically significant relationships and interpreted as negligible (0.00-0.10), weak (0.10-0.39), moderate (0.40-0.69), strong (0.70-0.89), and very strong (0.90-1.00). (3) Results: Eighteen articles remained eligible, with an average quality score of 76% ± 14 on the Joanna Briggs Institute critical appraisal index. The strongest correlations reported included time-to-bottom, time-to-peak force, knee extension peak power at 180 °/s, and squat jump height. (4) Conclusions: The conclusions drawn from this study suggest that, to maximize CMJ performance, priority should be given to movement biomechanics and lower-body power whilst considering individual braking-phase strategies. These findings may inform training programs aimed not only at enhancing athletic performance but also at reducing injury risks associated with poor jumping mechanics in team sports.